Integrating ecosystem services value for sustainable land-use management in semi-arid region. (10th June 2018) - Rao, Yingxue; Zhou, Min; Ou, Guoliang; Dai, Deyi; Zhang, Lu; Zhang, Zuo; Nie, Xin; Yang, Chun
Abstract: In this study, an inexact multi-objective optimization model integrated with ecosystem service value was developed for supporting sustainable land-use management in Took Mu Qinqi in the northeast of Inner Mongolia Province, China. It was an attempt to incorporate ecosystem service evaluation model within a general modeling framework in typical semi-arid region. The ecosystem service value was modified according to the development of eco-environment and social economy in Took Mu Qinqi based on the study of land ecosystem service value in China. The modified ecosystem service value provided input parameters for the optimization model. The results showed that the ecosystem service value of grassland was the highest among the six land-use categories, with about 97% and 83% of the total value for East and West Took Mu Qinqi, respectively. It indicated that grassland played an important role in ecosystem service. The results also showed that the total economic benefit produced by the optimal land use pattern increased by [11.5, 12.6], [5.66, 6.36] × 10 12 RMB ¥ compared with the current land-use pattern for East, West Took Mu Qinqi, respectively. The total ecosystem service value produced by the optimal land-use pattern also increased by [5.9, 9.1], [3.4, 4.5] × 10 12 RMB ¥ compared with that produced by the current land-use pattern for East, West Took Mu Qinqi, respectively. It indicated that the optimal land-use pattern generated by the multi-objective model was better than the current land-use pattern either from the point of economic benefit or from the point of ecological benefit. The optimization model of land-use structure based on ecosystem service value could satisfy the social, economical, and environmental development, which provided a new way to solve the key technical problem in land-use planning in typical semi-arid region. Graphical abstract: Image Highlights: An inexact multi-objective optimization model integrated with ecosystem services value was developed. The developed model was applied to a case of sustainable land use management in the typical semi-arid region. The optimal land use pattern generated by the developed model was better than the current land use pattern.